A perovskite solar cell and a method for manufacturing the same

During the production process of perovskite solar cells, a perovskite layer with light trapping function is formed by using the mixed anti-solvent dropping method, which solves the problem of solar light reflection caused by the flattening of perovskite layer in perovskite solar cells, and improves the problem of improvement. The effect of conversion efficiency.

CN112467039BActive Publication Date: 2025-02-11LONGI GREEN ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011305748.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-19
Publication Date
2025-02-11
Estimated Expiration
2040-11-19

AI Technical Summary

Technical Problem

The flat perovskite layer of perovskite solar cells causes the reflection of solar light, hindering the full absorption and utilization of solar light, thereby reducing the conversion efficiency.

Method used

By adding mixed anti-solvent dropwise during the perovskite precursor solution layer, a perovskite layer with light trapping function is formed. The mixed antisolvent includes the first antisolvent and the second antisolvent mixed in bulk. The solubility of the perovskite material in the second antisolvent is greater than the solubility in the first antisolvent, resulting in the precipitation of the perovskite precursor solution in different regions. Perovskite seed crystals form a depression structure.

Benefits of technology

It improves the absorption and utilization of solar light by perovskite solar cells, improves conversion efficiency, and simplifies the process flow and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112467039B_ABST
    Figure CN112467039B_ABST
Patent Text Reader

Abstract

The present invention discloses a perovskite solar cell and a method for making the same, and relates to the field of photovoltaic technology, so as to make a perovskite layer with a light trapping function and improve the conversion efficiency of the perovskite solar cell. The preparation of the perovskite layer comprises the following steps: forming a perovskite precursor solution layer on a substrate, dripping a mixed anti-solvent in the process of forming the perovskite precursor solution layer; then performing an annealing treatment to form a perovskite layer; wherein the mixed anti-solvent comprises a first anti-solvent and a second anti-solvent, the first anti-solvent and the second anti-solvent are immiscible or partially miscible at the temperature of forming the perovskite precursor solution layer, the first anti-solvent and the second anti-solvent are mixed, and the solubility of the perovskite material in the second anti-solvent is greater than the solubility of the perovskite material in the first anti-solvent. The perovskite solar cell and the method for making the same provided by the present invention are used for solar cell manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a perovskite solar cell and a manufacturing method thereof. Background Art

[0002] In the process of making perovskite solar cells, an anti-solvent method can be used to make a perovskite layer. The perovskite layer made by the anti-solvent method has uniform grain size and high surface flatness.

[0003] However, when sunlight enters the flat perovskite thin film structure, it will produce strong reflection. This strong reflection is not conducive to the full absorption and utilization of solar light by perovskite solar cells, and hinders the improvement of the conversion efficiency of perovskite solar cells. Summary of the invention

[0004] The object of the present invention is to provide a perovskite solar cell and a method for manufacturing the same, so as to manufacture a perovskite layer with a light trapping function and improve the conversion efficiency of the perovskite solar cell.

[0005] In a first aspect, the present invention provides a method for manufacturing a perovskite solar cell. The manufacturing of the perovskite layer comprises the following steps:

[0006] A perovskite precursor solution layer is formed on a substrate, and a mixed anti-solvent is added dropwise during the process of forming the perovskite precursor solution layer; and then an annealing treatment is performed to form a perovskite layer; wherein,

[0007] The mixed anti-solvent includes a first anti-solvent and a second anti-solvent, the first anti-solvent and the second anti-solvent are mixed, the first anti-solvent and the second anti-solvent are immiscible or partially miscible at a temperature for forming the perovskite precursor solution layer, and the solubility of the perovskite material in the second anti-solvent is greater than the solubility of the perovskite material in the first anti-solvent.

[0008] When the above technical solution is adopted, since the mixed anti-solvent is dripped in the process of forming the perovskite precursor solution layer, the perovskite seed crystals are precipitated on the surface where the perovskite precursor solution contacts the mixed anti-solvent. The mixed anti-solvent in contact with the perovskite precursor solution includes a first anti-solvent and a second anti-solvent mixed in the bulk phase, so that the contact interface between the perovskite precursor solution and the mixed anti-solvent is divided into a first region in contact with the first anti-solvent and a second region in contact with the second anti-solvent.

[0009] Based on the rule that the smaller the solubility of the perovskite material in the anti-solvent, the easier it is for the perovskite precursor solution in contact with the anti-solvent to precipitate perovskite seed crystals, and the faster the precipitation speed, the larger the grains; when the solubility of the perovskite material in the second anti-solvent is greater than the solubility of the perovskite material in the first anti-solvent, the perovskite precursor solution in the first region is easier to precipitate perovskite seed crystals, and the precipitation speed of the perovskite seed crystals is faster and the grain size is larger; the perovskite precursor solution in the second region is more difficult to precipitate perovskite seed crystals, and the precipitation speed of the perovskite seed crystals is slower and the grain size is smaller. In this case, the perovskite in the perovskite precursor solution is preferentially precipitated in the first region, and part of the perovskite precursor solution in the second region is consumed, so that a concave structure is formed under the second region. At this time, the formed perovskite layer has a textured morphology and light trapping function, which can improve the absorption and utilization of solar light by the perovskite solar cell, thereby improving the conversion efficiency of the perovskite solar cell.

[0010] In some possible implementations, the mixed anti-solvent further includes a non-ionic surfactant, wherein the mass of the non-ionic surfactant is 3% to 8% of the total mass of the mixed anti-solvent. At this time, the non-ionic surfactant can change the surface properties of the first anti-solvent and the second anti-solvent, improve the dispersibility of the second anti-solvent in the first anti-solvent, and stably disperse the second anti-solvent in the first anti-solvent, so that the first anti-solvent and the second anti-solvent are mixed in the body.

[0011] In some possible implementations, the nonionic surfactant includes one or more of lauryl alcohol polyoxyethylene ether, 12-14 carbon primary alcohol polyoxyethylene ether, and 12-14 carbon secondary alcohol polyoxyethylene ether.

[0012] In some possible implementations, the mixed anti-solvent is an emulsion formed by ultrasonic dispersion of the first anti-solvent and the second anti-solvent. At this time, the second anti-solvent is physically dispersed in the first anti-solvent to form a bulk mixed solution. This method of ultrasonic dispersion to form a bulk mixed solution can introduce less foreign matter, reduce changes in the properties of the first anti-solvent and the second anti-solvent, and thus reduce the adverse effects on the precipitation of perovskite grains.

[0013] In some possible implementations, the density ratio of the first anti-solvent and the second anti-solvent is (0.8-1.2):(0.8-1.2). At this time, the densities of the first anti-solvent and the second anti-solvent are similar. When the second anti-solvent is dispersed in the first anti-solvent, it can be better dispersed in the first anti-solvent, which can reduce the problem of the second anti-solvent sinking to the bottom or floating on the surface of the first anti-solvent.

[0014] In some possible implementations, the relative polarity of the first anti-solvent is less than 4.5, and the relative polarity of the second anti-solvent is less than 7.5. At this time, the relative polarity of the second anti-solvent is larger, and the relative polarity of the first anti-solvent is smaller. On the one hand, the bulk mixing of the first anti-solvent and the second anti-solvent can be achieved by utilizing the relative polarity difference between the first anti-solvent and the second anti-solvent. On the other hand, the solvent of the perovskite precursor solution is generally a solvent with a relative polarity greater than 6. Relative to the first anti-solvent, the polarity of the second anti-solvent is closer to the polarity of the solvent of the perovskite precursor solution, so that the solubility of the perovskite material in the second anti-solvent is larger, thereby making it easy for the second region to form a recessed region.

[0015] In some possible implementations, the volume percentage of the first anti-solvent contained in the mixed anti-solvent is greater than or equal to 70%. In this case, the problem of excessive roughness of the perovskite film, more grain boundaries, and poor film continuity caused by a small content of the first anti-solvent can be avoided, thereby ensuring that the perovskite layer has a light trapping structure and a high film quality.

[0016] In some possible implementations, the first anti-solvent includes one or more of n-hexane, cyclohexane, n-heptane, isooctane, cyclopentane, pentane, and ether. The relative polarity of these first anti-solvents is significantly different from the relative polarity of the solvent of the perovskite precursor solution. When the perovskite precursor solution contacts these first anti-solvents, perovskite seed crystals can be precipitated relatively easily and quickly.

[0017] In some possible implementations, the second anti-solvent includes one or more of acetonitrile, methanol, N,N-dimethylformamide, dimethyl sulfoxide, and nitrobenzene.

[0018] In some possible implementations, the solvent of the perovskite precursor solution contained in the perovskite precursor solution layer includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, and acetonitrile.

[0019] In some possible implementations, a method of forming the perovskite precursor solution layer includes one of blade coating, spin coating, drop coating, inkjet coating, rotogravure coating, spray coating, and roller coating.

[0020] In a second aspect, the present invention provides a perovskite solar cell. The perovskite solar cell is manufactured using the method for manufacturing a perovskite solar cell described in the first aspect or any possible implementation of the first aspect.

[0021] The beneficial effects of the perovskite solar cell provided in the second aspect can refer to the beneficial effects of the method for manufacturing a perovskite solar cell described in the first aspect or any possible implementation of the first aspect, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0023] Figure 1 to Figure 3 A schematic diagram of various stages of preparing a perovskite layer by an anti-solvent method in the prior art;

[0024] Figures 4 to 9 A schematic diagram of each stage of the method for manufacturing a perovskite solar cell provided by an embodiment of the present invention;

[0025] Fig.10 Schematic diagram of a mixed anti-solvent in a bulk phase mixing state provided by an embodiment of the present invention.

[0026] Figure 1 to Figure 3 In the figure, 11-substrate, 12-electron transport layer, 13-perovskite precursor solution layer, 131-perovskite seed layer, 132-perovskite layer, and 14-antisolvent layer.

[0027] Figures 4 to 10 In the figure, 21-substrate, 22-electron transport layer, 23-perovskite precursor solution layer, 231-perovskite seed layer, 232-perovskite layer, 24-mixed anti-solvent layer, 241-first anti-solvent, 242-second anti-solvent, 25-hole transport layer, 26-transparent conductive layer, 27-electrode. DETAILED DESCRIPTION

[0028] In order to clearly describe the technical solutions of the embodiments of the present invention, in the embodiments of the present invention, words such as "first" and "second" are used to distinguish the same or similar items with substantially the same functions and effects. Those skilled in the art can understand that words such as "first" and "second" do not limit the quantity and execution order, and words such as "first" and "second" do not necessarily limit the difference.

[0029] It should be noted that, in the present invention, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.

[0030] In the present invention, "at least one" means one or more, and "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b or c can mean: a, b, c, the combination of a and b, the combination of a and c, the combination of b and c, or the combination of a, b and c, where a, b, c can be single or multiple.

[0031] Perovskite is a light-absorbing material used in solar cells, and can be used to make perovskite solar cells. In the past decade, perovskite solar cells have developed rapidly, and the conversion efficiency has reached 25.2%, which is close to the conversion efficiency of crystalline silicon cells. And in the next few years, the conversion efficiency of perovskite solar cells is expected to exceed 30%.

[0032] At present, the research focus on improving the conversion efficiency of perovskite solar cells is mainly on surface and interface passivation, defect control, component regulation and film quality improvement. Light trapping structure plays a pivotal role in improving the conversion efficiency of perovskite solar cells. However, the research on the light trapping structure on the surface of perovskite solar cells is still very insufficient.

[0033] Figure 1-Figure 3 The process of making a perovskite layer by the anti-solvent method is exemplified. In the process of making a perovskite layer by the anti-solvent method, a solvent with weak polarity and that does not dissolve perovskite, such as chlorobenzene, toluene, and ether, is usually selected as an anti-solvent. The steps of making a perovskite layer by the anti-solvent method mainly include: applying a perovskite precursor solution on a substrate 11 having an electron transport layer 12 to form a perovskite precursor solution layer 13. Afterwards, an anti-solvent is applied on the perovskite precursor solution layer 13 to form an anti-solvent layer 14.

[0034] like Figure 1-Figure 3As shown, since the solubility of the perovskite material in the anti-solvent is very small, after the anti-solvent is applied, the surface where the perovskite precursor solution layer 13 contacts the anti-solvent layer 14 will quickly precipitate perovskite seed crystals to form a perovskite seed crystal layer 131. Since the anti-solvent layer 14 is a solution layer with uniform composition, under the action of the anti-solvent layer 14 with uniform composition, a layer of perovskite seed crystals 131 with uniform grain size can be precipitated on the surface of the perovskite precursor solution layer 13. Under the induction of the perovskite seed crystal layer 131, the perovskite in the perovskite precursor solution layer 13 is uniformly precipitated and grown, and finally a perovskite layer 132 with uniform grain size and relatively flat surface is obtained.

[0035] Although a flat perovskite layer is conducive to the preparation of a hole transport layer and an electrode on the perovskite layer, the flat film structure will cause strong reflection, which is not conducive to the full absorption and utilization of sunlight by perovskite solar cells, and hinders the improvement of the conversion efficiency of perovskite solar cells.

[0036] In order to solve the above technical problems, an embodiment of the present invention provides a perovskite solar cell. The perovskite solar cell has a light-trapping structure with a textured morphology. And the light-trapping structure is formed in the process of making the perovskite layer, and there is no need to add steps in the process of making the perovskite solar cell, thereby simplifying the process flow and reducing the process cost. The perovskite solar cell can be an organic-inorganic hybrid perovskite solar cell, an inorganic perovskite solar cell, or an organic perovskite solar cell.

[0037] The embodiment of the present invention also provides a method for manufacturing the above-mentioned perovskite solar cell. Figure 4-Figure 9 The following is a schematic diagram showing the various stages of the method for manufacturing a perovskite solar cell according to an embodiment of the present invention. Figure 4-Figure 9 The method for manufacturing a perovskite solar cell provided by an embodiment of the present invention is as follows.

[0038] like Figure 4 As shown, a substrate 21 is provided. The substrate 21 is a conductive substrate. Specifically, the substrate 21 can be any one of tin-doped indium oxide (ITO) transparent conductive glass, zinc-doped indium oxide (IZO) transparent conductive glass, tungsten-doped indium oxide (IWO) transparent conductive glass, titanium-doped indium oxide (ITIO) transparent conductive glass, fluorine-doped tin oxide (FTO) transparent conductive glass, and aluminum-doped zinc oxide (AZO) transparent conductive glass. In practical applications, the above-mentioned substrate 21 can be obtained by purchasing, or it can be prepared by itself through processes such as magnetron sputtering.

[0039] In order to facilitate the subsequent processing of the substrate 21, the substrate 21 can be cleaned. In practical applications, the substrate 21 is ultrasonically cleaned in a cleaning agent, water, acetone, and isopropanol for 30 minutes, then rinsed with ethanol, dried with dry air, and treated with ultraviolet ozone for 15 minutes to clean the surface of the substrate 21.

[0040] like Figure 5 As shown, an electron transport layer 22 is formed on a clean substrate 21. The material of the electron transport layer 22 can be any one of SnO2, TiO2, [6,6]-phenyl-C61-butyric acid isomethyl ester (PCBM), but is not limited thereto. The preparation process of the electron transport layer 22 can be spin coating, evaporation, etc., but is not limited thereto.

[0041] For example, a 2.67 wt % SnO 2 aqueous solution may be spin coated on the substrate 21 at a rotation speed of 4000 rpm, and then dried at 150° C. for 30 min after spin coating for 30 seconds to obtain an electron transport layer 22 made of SnO 2 with a thickness of 50 nm to 100 nm.

[0042] like Figure 6a-6c As shown, a perovskite precursor solution layer 23 is formed on the electron transport layer 22, and a mixed anti-solvent is added dropwise during the formation of the perovskite precursor solution layer 23; then an annealing treatment is performed to form a perovskite layer 232. The mixed anti-solvent includes a first anti-solvent 241 and a second anti-solvent 242 mixed in bulk phase. At the temperature at which the perovskite precursor solution layer is formed, the first anti-solvent 241 and the second anti-solvent 242 are immiscible or partially miscible, and the solubility of the perovskite material in the second anti-solvent 242 is greater than the solubility of the perovskite material in the first anti-solvent 241. Fig.10 As shown, bulk phase mixing refers to the mixing of the first anti-solvent 241 and the second anti-solvent 242 as two-phase materials in a non-stratified manner.

[0043] Figure 6a-6c The schematic diagram of forming a perovskite precursor solution layer on the electron transport layer and dropping a mixed anti-solvent during the process of forming the perovskite precursor solution layer to precipitate perovskite grains and form a perovskite film is shown. Figure 6a As shown, a perovskite precursor solution layer 23 is formed on the electron transport layer 22, and a mixed anti-solvent is added dropwise during the formation of the perovskite precursor solution layer 23. Since the mixed anti-solvent includes a first anti-solvent 241 and a second anti-solvent 242 mixed in bulk phase, after the perovskite precursor solution layer 23 contacts the mixed anti-solvent layer 24, the contact interface is divided into a first region contacting the first anti-solvent 241 and a second region contacting the second anti-solvent 242.

[0044] like Figure 6bAs shown, due to the dripping of the mixed anti-solvent in the process of forming the perovskite precursor solution layer 23, the part of the perovskite precursor solution layer 23 in contact with the mixed anti-solvent layer 24 precipitates a perovskite seed crystal layer 231. Specifically, based on the rule that the smaller the solubility of the perovskite material in the anti-solvent, the easier it is for the perovskite precursor solution in contact with the anti-solvent to precipitate perovskite seed crystals, and the faster the precipitation speed, the larger the grain size; when the solubility of the perovskite material in the second anti-solvent 242 is greater than the solubility of the perovskite material in the first anti-solvent 241, the perovskite precursor solution in the first region is easier to precipitate perovskite seed crystals, and the speed of precipitating perovskite seed crystals is faster and the grain size is larger; the perovskite precursor solution in the second region is more difficult to precipitate perovskite seed crystals, and the speed of precipitating perovskite seed crystals is slower and the grain size is smaller. The perovskite in the perovskite precursor solution is preferentially precipitated under the first region, so that a concave structure is formed under the second region, and there is no perovskite seed crystal in the concave structure. Based on this, the perovskite seed crystal layer 231 is a thin film with a concave structure. Figure 6c As shown, under the induction of the perovskite seed layer 231 with a concave structure, the perovskite in the perovskite precursor solution layer 23 continues to precipitate, and preferentially crystallizes and grows below the first area, and consumes the perovskite precursor solution below the second area until all the perovskite is precipitated. After annealing, a perovskite layer 232 is formed. It can be seen that the perovskite layer 232 formed in the embodiment of the present invention has a concave structure with a textured morphology, has a light trapping function, can improve the absorption and utilization of solar light by the perovskite solar cell, and thus improve the conversion efficiency of the perovskite solar cell.

[0045] Compared with the formation of the perovskite layer 232 by natural crystallization without using an anti-solvent, the formation of the perovskite layer 232 by using a mixed anti-solvent provided in the embodiment of the present invention can avoid the problems of slow crystallization speed, uncontrolled grain size, crystal quality, etc. during natural crystallization, and greatly reduce the probability of defects such as cracks and holes in the manufactured perovskite layer 232. In the perovskite layer 232 manufactured in the embodiment of the present invention, the crystallization speed of the perovskite precursor solution is relatively fast, and the film quality of the perovskite layer 232 is equivalent to that when a single anti-solvent is used. It is only after adding the second anti-solvent 242 that the local crystallization speed of the perovskite precursor solution is relatively slow, and some concave structures with light trapping function are formed on the well-crystallized perovskite film due to the slow crystallization speed.

[0046] It should be understood that before making the perovskite precursor solution layer 23, a perovskite precursor solution can be prepared for standby use. The solute of the perovskite precursor solution can be designed according to the material of the perovskite layer 232 to be made. For example, the solute of the perovskite precursor solution can be formamidine hydroiodide (FAI) and PbI2. The solute of the perovskite precursor solution can also be formamidine hydrobromide (FABr) and lead iodide (PbI2). The solute of the perovskite precursor solution can select an organic solvent with a relative polarity greater than 6.0. Specifically, the solvent of the perovskite precursor solution can be one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), acetonitrile, and is not limited thereto. Preferably, DMF and DMSO can be selected as a mixed solvent for the perovskite precursor solution.

[0047] Exemplarily, the method for preparing a perovskite precursor solution may include: dissolving 206.4 mg of formamidine hydroiodide (FAI), 27.0 mg of methylamine bromide (MABr), 608.6 mg of PbI2, and 88.2 mg of PbBr2 in 1 ml of a mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). The volume ratio of DMF to DMSO is 4:1 to form a mixed solution. Then, 52.2 μl of CsI DMSO solution (390 mg / ml) is added to the mixed solution, and heated and stirred at 60°C for 2 hours to obtain a perovskite precursor solution.

[0048] Before the mixed anti-solvent is added dropwise, a mixed anti-solvent can be prepared for standby use. The mixed anti-solvent includes a first anti-solvent and a second anti-solvent mixed in bulk phase, the first anti-solvent and the second anti-solvent are immiscible or partially miscible at a temperature for forming the perovskite precursor solution layer, and the solubility of the perovskite material in the second anti-solvent is greater than the solubility of the perovskite material in the first anti-solvent.

[0049] In order to make the first anti-solvent and the second anti-solvent form a mixed state, the first anti-solvent and the second anti-solvent that are partially miscible can be selected for preparation, or the first anti-solvent and the second anti-solvent that are immiscible can be selected for preparation.

[0050] When a mixed antisolvent is prepared using a partially miscible first antisolvent and a second antisolvent, the two are in a partially miscible state within the dissolution temperature range (or the dissolution temperature point), and the two are in a completely miscible state outside the dissolution temperature range. Based on this situation, the mixed antisolvent can be stored at a temperature outside the dissolution temperature range, at which time, during the storage process, it is in a stable completely miscible state. When a mixed antisolvent is used, the temperature of the mixed antisolvent can be controlled within the dissolution temperature range so that the first antisolvent and the second antisolvent in the mixed antisolvent are in a bulk mixed state. When a mixed antisolvent is used, the temperature of the substrate 21 with the electron transport layer 22 can also be controlled within the dissolution temperature range of the mixed antisolvent. When the mixed antisolvent is added dropwise to the perovskite precursor solution on the substrate 21, the temperature of the mixed antisolvent changes rapidly, the solution phases, and the second antisolvent precipitates in the first antisolvent to form a mixed antisolvent of bulk phase mixing. Of course, in order to ensure that the first antisolvent and the second antisolvent are always in a bulk mixed state before and during use of the mixed antisolvent, the temperatures of the mixed antisolvent to be used and the substrate 21 can both be controlled within the dissolution temperature range of the mixed antisolvent.

[0051] When a mixed antisolvent is configured using an immiscible first antisolvent and a second antisolvent, a nonionic surfactant can be added to the mixed antisolvent formed by the first antisolvent and the second antisolvent to form a mixed antisolvent in bulk phase. At this time, the nonionic surfactant can change the surface properties of the first antisolvent and the second antisolvent, improve the dispersibility of the second antisolvent in the first antisolvent, and stably disperse the second antisolvent in the first antisolvent, so that the first antisolvent and the second antisolvent are mixed in bulk phase.

[0052] Specifically, the nonionic surfactant may include one or more of lauryl alcohol polyoxyethylene ether, 12-14 carbon primary alcohol polyoxyethylene ether, and 12-14 carbon secondary alcohol polyoxyethylene ether, but is not limited thereto. The mass of these nonionic surfactants is 3% to 8% of the total mass of the mixed anti-solvent. For example, the mass of the nonionic surfactant may be 3%, 4%, 5%, 5.6%, 6%, 7%, 8%, etc. of the total mass of the mixed anti-solvent.

[0053] When a mixed antisolvent is configured using an immiscible first antisolvent and a second antisolvent, the first antisolvent and the second antisolvent can also be dispersed into an emulsion by ultrasonic dispersion. At this time, the second antisolvent is dispersed in the first antisolvent by physical means to form a bulk mixed solution. This method of ultrasonic dispersion to form a bulk mixed solution can introduce less foreign matter, reduce changes in the properties of the first antisolvent and the second antisolvent, and thus reduce the adverse effects on the precipitation of perovskite grains.

[0054] It should be understood that, although the ultrasonic dispersion method can make the first anti-solvent and the second anti-solvent form a mixed anti-solvent in which the first anti-solvent and the second anti-solvent are mixed in bulk phase, the state of such bulk phase mixing is not stable and is only bulk phase mixing in a short time. Even so, for the anti-solvent film forming process which is usually completed within one minute, the short dispersion time is sufficient, which is enough for the perovskite precursor solution layer 23 to complete the process of precipitating perovskite grains.

[0055] The density ratio of the first antisolvent and the second antisolvent is (0.8-1.2): (0.8-1.2). Exemplarily, the density ratio of the first antisolvent and the second antisolvent can be 0.8:1.2, 0.9:1.1, 1.0:1.0, 1.1:0.9, 1.2:0.8, 0.8:1.1, 0.9:0.8, 1.0:1.2 or 1.2:1.0, etc. At this time, the densities of the first antisolvent and the second antisolvent are similar. When the second antisolvent is dispersed in the first antisolvent, it can be better dispersed in the first antisolvent, which can reduce the problem of the second antisolvent sinking to the bottom or floating on the surface of the first antisolvent.

[0056] In the process of preparing the mixed anti-solvent, it is necessary not only to ensure that the first anti-solvent and the second anti-solvent are mixed in the bulk phase, but also to ensure that the solubility of the perovskite material in the second anti-solvent is greater than the solubility of the perovskite material in the first anti-solvent. At this time, in order to realize the difference in solubility of the first anti-solvent and the second anti-solvent for the perovskite material, the first anti-solvent can select a solvent with a relative polarity less than 4.5, and the second anti-solvent can select a solvent with a relative polarity less than 7.5. At this time, the relative polarity of the second anti-solvent is large, and the relative polarity of the first anti-solvent is small. On the one hand, the bulk phase mixing of the two can be achieved by utilizing the relative polarity difference between the first anti-solvent and the second anti-solvent. On the other hand, the solvent of the perovskite precursor solution is usually a solvent with a relative polarity greater than 6. Relative to the first anti-solvent, the polarity of the second anti-solvent is closer to the polarity of the solvent of the perovskite precursor solution, so that the solubility of the perovskite material in the second anti-solvent is large, and the second region is easy to form a recessed region.

[0057] In actual requirements, the first anti-solvent that meets the above requirements may include one or more of n-hexane, cyclohexane, n-heptane, isooctane, cyclopentane, pentane, and ether, and is not limited thereto. The relative polarity of these first anti-solvents is quite different from the relative polarity of the solvent of the perovskite precursor solution. When the perovskite precursor solution contacts these first anti-solvents, perovskite seed crystals can be precipitated relatively easily and quickly. Preferably, the first anti-solvent can select n-hexane or n-heptane, which can cause the perovskite precursor solution in contact therewith to precipitate perovskite seed crystals. The second anti-solvent that meets the above requirements may include one or more of acetonitrile, methanol, N,N-dimethylformamide, dimethyl sulfoxide, and nitrobenzene. Preferably, acetonitrile and methanol can be selected as the second anti-solvent.

[0058] The volume percentage of the first anti-solvent contained in the above-mentioned mixed anti-solvent is greater than or equal to 70%. For example, the volume percentage of the first anti-solvent and the second anti-solvent contained in the mixed anti-solvent can be 70:30, 75:25, 80:20, 82:18, 86:14, 90:10, 95:5, 99:1, etc. When the content of the second anti-solvent is too large, the roughness of the perovskite layer 232 will be too large, there will be more grain boundaries, the continuity of the film will be poor, and the solution will cause the perovskite solar cell to leak electricity, affecting the conversion efficiency. When the mixed anti-solvent is configured according to the above-mentioned proportion, the problem of excessive roughness of the perovskite film, more grain boundaries, and poor continuity of the film caused by the low content of the first anti-solvent can be avoided, thereby ensuring that the perovskite layer 232 has a light trapping structure and a higher film quality.

[0059] It should be noted that, when the polarity of the second anti-solvent is greater, its dissolving effect on the already crystallized perovskite grains is stronger. Therefore, the amount of the second anti-solvent added in the mixed anti-solvent can be reduced as its polarity increases. The content of the second anti-solvent in the above-mentioned mixed anti-solvent is related to the density of the recessed structure of the perovskite layer 232. In practical applications, the crystallization rate of the perovskite layer 232 and the morphology of the film surface can be adjusted by adjusting the content of the second anti-solvent, and the density and size of the recessed structure on the surface of the perovskite layer 232 can be adjusted, and finally the best light trapping effect can be achieved.

[0060] The method of forming the perovskite precursor solution layer 23 may include one of blade coating, spin coating, drop coating, inkjet coating, rotogravure coating, spray coating and roller coating.

[0061] Exemplarily, when a spin coating process is used to form a perovskite precursor solution layer 23, it can be carried out in a nitrogen glove box with a water content of less than 0.001‰ and an oxygen content of less than 0.001‰. In the specific operation, the substrate 21 having the electron transport layer 22 is placed in a nitrogen glove box, and the prepared perovskite precursor solution is spin-coated on the substrate 21. The spin coating process is specifically as follows: the first step, 1000rpm (acceleration: 200rpm / s), spin coating for 10 seconds; the second step, 6000rpm (acceleration 2000rpm / s), spin coating for 30 seconds. 8s-20s before the end of the second step of spin coating, 150μl of mixed anti-solvent is added to the perovskite precursor solution. After the spin coating is completed, heat at 120℃-180℃ for 20min-40min to obtain a perovskite layer 232.

[0062] like Figure 7As shown, a hole transport layer 25 is formed on the perovskite layer 232. The hole transport layer 25 may be made of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] amine), abbreviated as PTAA), 2,2',7,7'-tetrakis (di-p-tolylamino) spiro-9,9'-bifluorene (Spiro-TTB), etc. The thickness of the hole transport layer 25 can be 5nm-100nm. The process for forming the hole transport layer 25 can be any one of spin coating, spray coating, magnetron sputtering process, and thermal evaporation coating process, and is not limited thereto. It should be understood that in the manufacture of the above-mentioned perovskite solar cell, the electron transport layer 22 is first manufactured, and then the perovskite layer 232 and the hole transport layer 25 are manufactured. In some perovskite solar cells, the hole transport layer 25 can also be manufactured first, and then the perovskite layer 232 and the electron transport layer 22 are manufactured.

[0063] For example, when the hole transport layer 25 is made by spin coating, a Spiro-OMeTAD chlorobenzene solution with a concentration of 72.3 mg / ml is spin coated on the perovskite layer 232 at 4000 rpm for 30 seconds without drying.

[0064] like Figure 8 As shown, a transparent conductive layer 26 is formed on the hole transport layer 25, and the material of the transparent conductive layer 26 can be one or more of tin-doped indium oxide (ITO), zinc-doped indium oxide (IZO), tungsten-doped indium oxide (IWO), titanium-doped indium oxide (ITIO), fluorine-doped tin oxide (FTO), and aluminum-doped zinc oxide (AZO). The thickness of the transparent conductive layer 26 can be 50nm-150nm. The process of forming the transparent conductive layer 26 can be a magnetron sputtering process, a thermal evaporation process, etc. It should be understood that in some perovskite solar cells, the transparent conductive layer 26 can also be omitted.

[0065] like Fig. 9 As shown, an electrode 27 is fabricated on the transparent conductive layer 26. Specifically, the material of the electrode 27 may be a metal with good conductivity, such as silver or copper. The process for fabricating the electrode 27 may be screen printing, evaporation, sputtering, and the like.

[0066] For example, the transparent conductive layer 26 may be 5nm-8nm thick MoO3 was evaporated at a speed of 1000 nm to match the energy level of the electrode 27 with the hole transport layer 25. Then, 80nm thick Au was evaporated. During the Au evaporation process, the first 10nm was evaporated at a speed of After 70nm, the evaporation rate is

[0067] In order to verify the performance of the perovskite solar cell manufactured by the method for manufacturing a perovskite solar cell provided in the embodiment of the present invention, the following is a description by comparing the embodiment and the comparative example with each other.

[0068] Embodiment 1

[0069] The method for manufacturing a perovskite solar cell provided in this embodiment is specifically described as follows:

[0070] The first step is to provide a FTO conductive glass, and ultrasonically tilt the FTO conductive glass in a cleaning agent, water, acetone, and isopropanol for 30 minutes, then rinse it with ethanol, blow it dry with dry air, and treat it with ultraviolet ozone for 15 minutes.

[0071] In the second step, a 2.67 wt% SnO2 aqueous solution was spin-coated on the FTO conductive glass at a rotation speed of 4000 rpm. After spin-coating for 30 seconds, the solution was dried at 150°C for 30 minutes to obtain an electron transport layer made of SnO2 with a thickness of 80 nm.

[0072] The third step is to place the conductive glass with the electron transport layer in a nitrogen glove box with a water content of less than 0.001‰ and an oxygen content of less than 0.001‰, and spin-coat the perovskite precursor solution on the electron transport layer. The spin coating process is as follows: the first step, 1000rpm (acceleration: 200rpm / s), spin coating for 10 seconds; the second step, 6000rpm (acceleration 2000rpm / s), spin coating for 30 seconds. 10s before the end of the second step of spin coating, add 150μl of mixed anti-solvent to the perovskite precursor solution. After the spin coating is completed, heat at 150℃ for 30min to obtain the perovskite layer.

[0073] n-Hexane is used as the first anti-solvent, and methanol is used as the second anti-solvent, and the volume percentage of n-hexane to methanol is 98:2. The relative polarity of n-hexane is 0.06, and the relative polarity of methanol is 6.60. The dissolution temperature of n-hexane and methanol is 51°C. Above 51°C, the two are completely miscible; below 51°C, the two will separate into phases. The conductive glass is heated so that the temperature of the mixed anti-solvent is 51°C during the dropwise addition of the mixed anti-solvent.

[0074] The fourth step is to spin-coat a Spiro-OMeTAD chlorobenzene solution with a concentration of 72.3 mg / ml on the perovskite layer at 4000 rpm for 30 seconds without drying to form a 50 nm thick hole transport layer.

[0075] In the fifth step, a 100 nm thick transparent conductive layer made of FTO is formed on the hole transport layer by a thermal evaporation process.

[0076] Step 6: On the transparent conductive layer 7nm thick MoO3 was evaporated at a speed of . Then, 80nm thick Au was evaporated. During the Au evaporation process, the evaporation speed of the first 10nm was After 70nm, the evaporation rate is

[0077] Embodiment 2

[0078] The method for manufacturing a perovskite solar cell provided in this embodiment is basically the same as the method for manufacturing a perovskite solar cell described in the first embodiment, except that:

[0079] In this embodiment, n-heptane is used as the first anti-solvent, nitrobenzene is used as the second anti-solvent, and the volume percentage of n-heptane to nitrobenzene is 99:1. The relative polarity of n-heptane is 0.20, the relative polarity of nitrobenzene is 6.30, and the dissolution temperature of n-heptane and nitrobenzene is 20.6°C. Above 20.6°C, the two are completely miscible, and below 20.6°C, the two phases are separated. The conductive glass is heated so that the temperature of the mixed anti-solvent is 20.6°C during the process of dripping the mixed anti-solvent.

[0080] Embodiment 3

[0081] The method for manufacturing a perovskite solar cell provided in this embodiment is basically the same as the method for manufacturing a perovskite solar cell described in the first embodiment, except that:

[0082] In this embodiment, n-hexane is used as the first anti-solvent, DMF is used as the second anti-solvent, and the volume percentage of n-hexane to DMF is 99.5:0.5. The relative polarity of n-hexane is 0.06, and the relative polarity of DMF is 6.4. n-hexane and DMF are immiscible, and DMF is dispersed in n-hexane for a short time by ultrasound to form an emulsion. The parameters of the ultrasonic process are: using an ultrasonic cell crusher, 22kHz, sinusoidal waveform, 600W power, 60°C, and ultrasonic dispersion for 15min. The mixed anti-solvent after ultrasonic dispersion is immediately added dropwise to the perovskite precursor solution being spin-coated.

[0083] Embodiment 4

[0084] The method for manufacturing a perovskite solar cell provided in this embodiment is basically the same as the method for manufacturing a perovskite solar cell described in the first embodiment, except that:

[0085] In this embodiment, ether is used as the first anti-solvent with a relative polarity of 2.90; DMSO is used as the second anti-solvent with a relative polarity of 7.20. The volume percentage of ether is 99.7%, and the volume percentage of DMSO is 0.3%. Ether and DMSO are immiscible solvents. 5wt% of lauryl alcohol polyoxyethylene ether as a dispersant is added to the mixed anti-solvent, and stirred for 30 minutes to form a mixed anti-solvent with a stable bulk phase mixture.

[0086] By observing the surface morphology of the perovskite solar cells produced in Examples 1 to 4, it is found that the surfaces of the perovskite solar cells produced in Examples 1 to 4 have a concave structure, forming a textured morphology and the grain size of the perovskite layer is relatively large.

[0087] Although the present invention is described herein in conjunction with various embodiments, in the process of implementing the claimed invention, those skilled in the art may understand and implement other variations of the disclosed embodiments by viewing the drawings, the disclosure, and the appended claims. In the claims, the word "comprising" does not exclude other components or steps, and "a" or "an" does not exclude a plurality of components. Certain measures are recorded in different dependent claims, but this does not mean that these measures cannot be combined to produce good results.

[0088] Although the present invention has been described in conjunction with specific features and embodiments thereof, it is apparent that various modifications and combinations may be made thereto without departing from the spirit and scope of the present invention. Accordingly, this specification and the accompanying drawings are merely exemplary illustrations of the present invention as defined by the appended claims and are deemed to cover any and all modifications, variations, combinations or equivalents within the scope of the present invention. Obviously, those skilled in the art may make various modifications and variations to the present invention without departing from the spirit and scope of the present invention. Thus, the present invention is intended to include such modifications and variations if they fall within the scope of the claims of the present invention and their equivalents.

Claims

1. A method for manufacturing a perovskite solar cell, characterized in that: The production of the perovskite layer includes the following steps: A perovskite precursor solution layer is formed on a substrate, and a mixed anti-solvent is added dropwise during the process of forming the perovskite precursor solution layer; and then an annealing treatment is performed to form a perovskite layer; the perovskite layer has a textured morphology; wherein, The mixed anti-solvent includes a first anti-solvent and a second anti-solvent that are mixed in bulk phase. The first anti-solvent and the second anti-solvent are immiscible or partially miscible at a temperature for forming the perovskite precursor solution layer, and the solubility of the perovskite material in the second anti-solvent is greater than the solubility of the perovskite material in the first anti-solvent; the first anti-solvent and the second anti-solvent are both anti-solvents for precipitating the perovskite material; the first anti-solvent includes one or more of n-hexane, cyclohexane, n-heptane, isooctane, cyclopentane, pentane, and ether; the second anti-solvent includes one or more of acetonitrile, methanol, N,N-dimethylformamide, dimethyl sulfoxide, and nitrobenzene.

2. The method for manufacturing a perovskite solar cell according to claim 1, characterized in that: The mixed anti-solvent further comprises a non-ionic surfactant; wherein the mass of the non-ionic surfactant is 3% to 8% of the total mass of the mixed anti-solvent.

3. The method for manufacturing a perovskite solar cell according to claim 2, characterized in that: The nonionic surfactant includes one or more of lauryl alcohol polyoxyethylene ether, 12-14 carbon primary alcohol polyoxyethylene ether, and 12-14 carbon secondary alcohol polyoxyethylene ether.

4. The method for manufacturing a perovskite solar cell according to claim 1, characterized in that: The mixed anti-solvent is an emulsion formed by dispersing the first anti-solvent and the second anti-solvent by ultrasonic wave.

5. The method for manufacturing a perovskite solar cell according to claim 1, characterized in that: The density ratio of the first anti-solvent to the second anti-solvent is (0.8-1.2): (0.8-1.2).

6. The method for manufacturing a perovskite solar cell according to claim 1, characterized in that: The relative polarity of the first anti-solvent is less than 4.5, and the relative polarity of the second anti-solvent is less than 7.

5.

7. The method for manufacturing a perovskite solar cell according to any one of claims 1 to 6, characterized in that: The volume percentage of the first anti-solvent contained in the mixed anti-solvent is greater than or equal to 70%.

8. The method for manufacturing a perovskite solar cell according to any one of claims 1 to 6, characterized in that: The solvent of the perovskite precursor solution contained in the perovskite precursor solution layer includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, and acetonitrile.

9. The method for manufacturing a perovskite solar cell according to any one of claims 1 to 6, characterized in that: The method of forming the perovskite precursor solution layer includes one of blade coating, spin coating, drop coating, inkjet coating, rotogravure coating, spray coating and roller coating.

10. A perovskite solar cell, characterized in that: The perovskite solar cell is manufactured by the method for manufacturing a perovskite solar cell according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-performance perovskite film, preparation method thereof and solar cell

    CN106784328A

  • Perovskite ink formulations

    GB201908046D0